Chemical diffusion coefficient calculation of U3+ in LiCl-KCl molten salt. (August 2016) - Zhou, Wentao; Zhang, Jinsuo
Abstract: Self-diffusion coefficient denotes the intrinsic diffusion of elements without the chemical gradient; generally, it is different from the chemical diffusion coefficient that is used in Fick's law. However, the self-diffusion coefficient can be converted to the chemical diffusion coefficient by considering the concentration-dependent activity coefficient of solute. In this study, the multiple time origins method was applied to calculate the self-diffusion coefficient of U 3+ in LiCl-KCl eutectic salt at different temperatures and concentrations. The chemical diffusion coefficient was obtained based on the calculated results and thermodynamic theory. Calculated results show that self-diffusion coefficient decreases with concentration however chemical diffusion coefficient indicates to change little initially but appears to increase followed by decrease later within the concentration range of 0–3 at%. Highlights: Calculated the self-diffusivity of UCl3 in LiCl-KCl molten salt. Derived the chemical diffusivity of UCl3 in LiCl-KCl molten salt. Self-diffusivity decreases with concentration. Chemical-diffusivity varies little initially then shows an increase by a decrease.